2019
DOI: 10.1186/s13550-019-0550-5
|View full text |Cite
|
Sign up to set email alerts
|

Molecular imaging of endothelial activation and mineralization in a mouse model of accelerated atherosclerosis

Abstract: Purpose Preclinical imaging of endothelial activation and mineralization using both positron emission tomography (PET) and magnetic resonance (MR) remains scarce. Procedures A group of uremic ApoE −/− (Ur), non-uremic ApoE −/− (NUr), and control C57Bl/6 J mice (Ctl) were investigated. Mineralization process was assessed using sodium fluoride ([18F]NaF) PET, and MR imaging combined with intravenous injection of MPIO-α… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…Regarding the question of which arterial wall compartment first experiences NaF-detectable microcalcifications, the Creager study demonstrated that NaF binds to microcalcifications formed by calcifying extracellular vesicles delivered from vascular smooth muscle cells, and it was shown in animal studies that exercise in hyperlipidemic mice (ApoE −/− ) with baseline aortic calcification is associated with a reduction in aortic NaF uptake, whereas the fold change in aortic calcification measured by CT remained constant [ 28 ]. Moreover, when comparing uremic ApoE −/− mice with non-uremic ApoE −/− mice or control mice, the heart and close-by aorta showed both early and sustained NaF-uptake, which may be associated with endothelial activation in segments with vascular remodeling [ 29 ]. The extent to which these studies in rodent models translate to humans is not clear.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the question of which arterial wall compartment first experiences NaF-detectable microcalcifications, the Creager study demonstrated that NaF binds to microcalcifications formed by calcifying extracellular vesicles delivered from vascular smooth muscle cells, and it was shown in animal studies that exercise in hyperlipidemic mice (ApoE −/− ) with baseline aortic calcification is associated with a reduction in aortic NaF uptake, whereas the fold change in aortic calcification measured by CT remained constant [ 28 ]. Moreover, when comparing uremic ApoE −/− mice with non-uremic ApoE −/− mice or control mice, the heart and close-by aorta showed both early and sustained NaF-uptake, which may be associated with endothelial activation in segments with vascular remodeling [ 29 ]. The extent to which these studies in rodent models translate to humans is not clear.…”
Section: Discussionmentioning
confidence: 99%
“…Animal model was established as previously described [16]. Male C57BL/6J mice (6 weeks old, 20 ± 2 g) and C57BL/6J ApoE −/− mice were obtained from Jackson Laboratory (Bar Harbor, ME, USA) and then kept in pathogen-free individual cages under 12-h day/night cycle at the temperature of 15–25°C in 50–60% humidity.…”
Section: Methodsmentioning
confidence: 99%
“…In vivo: human adipose engraftment mouse model; Ex vivo: human coronary arteries [117] WD: Western Diet; HD: Hypercholesterolemic Diet. Otherwise, recently, Rucher et al coupled MPIO-VCAM-1 magnetic resonance with [ 18 F]NaF PET in an ApoE −/− mouse model with chronic renal failure in order to identify both endothelial activation and microcalcifications [96]. This preclinical investigation opens new perspectives for the evaluation of the dynamic process of atherosclerosis by helping understand the relationship between inflammation, early mineralisation, which is known to detect high risk plaques, and vascular remodelling observed in this murine model.…”
Section: Imaging Of Vcam-1mentioning
confidence: 99%